Perception of parents of children with communication difficulties about inclusive education in Ibadan metropolis (2015)
Inclusive education represents an educational reform aiming at redesigning the general education structures to accommodate all learners with or without communication difficulties. However, the education of children with communication difficulties is influenced by several factors such as those factors that are resident in the home environment of a child with communication difficulties. Therefore, this study investigated the perception of parents of children with communication difficulties about inclusive education in Ibadan, Oyo state. Fifty-two (52) parents of children with communication difficulties who were purposively selected from three different centres educating children with special needs participated in the study. Three (3) research questions were raised and answered in the study. The study employed the use of descriptive research design. A self designed structured questionnaire tagged “Parents Perception on Inclusion Scale (α=.67)" was used for data collection. Data generated was analysed using descriptive statistics of bar chat and simple percentage as well as inferential statistics of Pearson product moment correlation and multiple regression. The findings revealed that educational qualification of parents of children with communication difficulties does not influence their perception about inclusive education for their children (r = 0.86, p<0.05); there is no composite relationship between parent's gender (Male or Female) and perception about inclusive education of children with communication difficulties (F(1.40) = 0.599, P<0.05). The findings also revealed that social environment has an impact on the perception and attitude towards inclusive education for children with communication difficulties. Based on the findings, it was recommended that positive attitudes towards people with communication difficulties should be adequately encouraged because increasing personal contact with people with communication difficulties will positively influence their access to education, employment and social activities.